Museu, informação artística e “poesia das coisas”: a divulgação artística em museus de arte - Moraes, Julia Nolasco Leitão de (2014)
This mainly theoretical research discusses art divulgation through art museums as an alternative of info-communication strategy for promoting meetings of visitors not acquainted with artistic universe and "the poetry of things". Thinking that artistic information is structured from the discourse of art and on art in the musealization process framework, we have gathered a bibliography, identified and analyzed principles that guide audience divulgation of this specific kind of information in the art museum context. Thus, the research has taken as challenges to discuss theoretical foundations underpinning the process of musealization in art museums and to propose a concept of artistic divulgation from scientific divulgation. Assuming that museums are propelling agents of familiarization and interrogation processes with and on the field of art, they can be configured as a privileged platform for constructing and exercising sensibility as well as critical appraisal, stimulating ways of contextual and reflexive apprehension capable to promote changes in visitors' everyday life. In that sense, museums must develop integrate actions and initiatives in a process of musealization, focusing on research and documentation in order to make possible to organize exhibitions which unveil the “poetry of things” and favour its resignification by different visitors.